REVIEW: A RECENT REVIEW IN APPLICATIONS OF HETEROCYCLIC COMPOUNDS AS ANTIMICROBIAL AGENT - D, Mohanambal; G, Sridevi; Antony S, Arul; R, Angayarkani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
A wide development in the field of multidrug resistance in antimicrobial activity which enhance the search for development of new medicinal drugs with high potential. Schiff base heterocyclic metal complex with imine moiety, act as important antimicrobial agents due to their versatile properties such as chelation, adaptability of fine structure for a specific biological action, and chemotheraptic drugs. Schiff base compounds derived from various heterocyclic platforms have been competently reviewed. Â 